Complex Network of Wnt Signaling Regulates Neuronal Migrations During Caenorhabditis elegans Development - Zinovyeva, Anna Y. (Genetics Society of America, 2008)
Members of the Wnt family of secreted glycoproteins regulate many developmental processes, including cell migration. We and others have previously shown that the Wnts egl-20, cwn-1, and cwn-2 are required for cell migration and axon guidance. However, the roles in cell migration of all of the Caenorhabditis elegans Wnt genes and their candidate receptors have not been explored fully. We have extended our analysis to include all C. elegans Wnts and six candidate Wnt receptors: four Frizzleds, the sole Ryk family receptor LIN-18, and the Ror receptor tyrosine kinase CAM-1. We show that three of the Wnts, CWN-1, CWN-2, and EGL-20, play major roles in directing cell migrations and that all five Wnts direct specific cell migrations either by acting redundantly or by antagonizing each other's function. We report that all four Frizzleds function to direct Q-descendant cell migrations, but only a subset of the putative Wnt receptors function in directing migrations of other cells. Finally, we find striking differences between the phenotypes of the Wnt quintuple and Frizzled quadruple mutants.